2018
DOI: 10.1093/epolic/eiy014
|View full text |Cite
|
Sign up to set email alerts
|

The productivity puzzle and misallocation: an Italian perspective

Abstract: Productivity has recently slowed down in many economies around the world. A crucial challenge in understanding what lies behind this "productivity puzzle" is the still short time span for which data can be analysed. An exception is Italy where productivity growth started to stagnate 25 years ago. Italy therefore offers an interesting case to investigate in search of broader lessons that may hold beyond local specific cities. We find that resource misallocation has played a sizeable role in slowing down Italian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…In-depth analysis of the mystery of low productivity growth in southern European countries, Gopinath et al [39] found that capital misallocation seriously hindered economic development and inhibited productivity growth. Furthermore, Calligaris et al [40] also proposed that resource misallocation hinders productivity. Han and Zhang [41] put forward that excessive government intervention is an important reason for resource misallocation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In-depth analysis of the mystery of low productivity growth in southern European countries, Gopinath et al [39] found that capital misallocation seriously hindered economic development and inhibited productivity growth. Furthermore, Calligaris et al [40] also proposed that resource misallocation hinders productivity. Han and Zhang [41] put forward that excessive government intervention is an important reason for resource misallocation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, small firms are considered an important engine for growth and job creation in developing countries. Distortions in the economy that prevent the most efficient firms from accessing capital and labour within this size group could have detrimental effects for the 1 See, for example, Calligaris et al (2018) for evidence from Italy; and Fujii and Nozawa (2013) for evidence from Japan. 2 Exceptions include Chen and Irarrazabal (2015), who find that misallocation decreased in Chile during the growth period following the crisis in the early 1980s, and that this was an important source of productivity growth.…”
Section: Introductionmentioning
confidence: 99%
“…Misallocation of capital has been on the rise since the turn of the millennium in several European countries (see e.g. Gopinath et al, 2017, Gamberoni et al, 2016and Calligaris et al, 2018. Our analysis focuses on the evolution of resource misallocation in the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…3 The larger the standard deviation, the higher the degree of misallocation. Calligaris (2015) and Calligaris et al (2018) also find steadily increasing misallocation in Italy.…”
Section: Modelmentioning
confidence: 92%
See 1 more Smart Citation